2009
DOI: 10.1111/j.1365-4632.2009.03490.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidermoid cysts: an exclusive palatal presentation and a case series

Abstract: Besides the previously reported locations, we present the first case occurring in the hard palate, measuring 5 x 3 cm in size along with melanin pigmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 5 publications
0
15
0
2
Order By: Relevance
“…Pathogenically, EOC can be divided into congenital and acquired types, without any clinical or histologic differences 9. Acquired factors include aberrant epithelial components in deep tissue due to trauma, inflammation or surgical complications which may be mechanisms of onset,10 while congenital EOC develop from inclusion of ectodermal tissue during embryogenesis 6. Previous trauma or surgical intervention was not encountered in our case suggesting a congenital epidermal cyst.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Pathogenically, EOC can be divided into congenital and acquired types, without any clinical or histologic differences 9. Acquired factors include aberrant epithelial components in deep tissue due to trauma, inflammation or surgical complications which may be mechanisms of onset,10 while congenital EOC develop from inclusion of ectodermal tissue during embryogenesis 6. Previous trauma or surgical intervention was not encountered in our case suggesting a congenital epidermal cyst.…”
Section: Discussionmentioning
confidence: 73%
“…There is only one report case in the literature of EOC localised in the hard palate that presented as a lobulated mass without any bone involvement 6. We report the first case of EOC localised in hard palate with bone involvement.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…4 Ravindranath et al reported epidermoid cyst to be most common in the lateral side of the neck and gingiva followed by the forehead region. 5 Dhabholkar et al reported 3 cases of dermoid cysts out of which 2 were located in the floor of the mouth and another in the midline of the neck. 6 Ultrasonography is the best investigation for these types of cyst.…”
Section: Discussionmentioning
confidence: 99%